The dusky gull (L. fuliginosus) and the swallow-tailed gull (L. furcatus). - Moynihan, M. (1962)
See: Moynihan, M. Hostile and sexual behavior patterns of South American and Pacific Laridae. Behaviour, Supplement 8. 598.338 MON (gen. coll.) BIB Now: 5165
English
Keywords: LR, BH -- The dusky gull (L. fuliginosus) and the swallow-tailed gull (L. furcatus). -- birds, lava gull, swallow tailed gull -- aves, piqueros, gaviota de lava, gaviota de cola bifurcada